2022
DOI: 10.3390/ijms23158422
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tin-Doped Three-Dimensional Flower-like Bismuth Tungstate with Enhanced Photocatalytic Activity

Abstract: Photocatalytic degradation of harmful organic matter is a feasible and environmentally friendly method. Bi2WO6 has become a hotspot of photocatalysts because of its unique layered structure and visible light response. In the present study, Sn doping was adopted to modified Bi2WO6 by hydrothermal method. The Sn-doped Bi2WO6 photocatalysts were characterized by XRD, SEM, TEM, BET, XPS, PL, and DRS, respectively. The results show that Sn-doped Bi2WO6 shows three-dimensional (3D) flower-like morphology, which is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The following supporting information can be downloaded at: https://www.mdpi.com/article/10.3390/molecules29122913/s1. References [41][42][43][44][45][46][47][48][49] are cited in the Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following supporting information can be downloaded at: https://www.mdpi.com/article/10.3390/molecules29122913/s1. References [41][42][43][44][45][46][47][48][49] are cited in the Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: . References [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%
“…It is important to carry out metal doping in a reasonable manner according to the specific requirements of each application. For example, Zhu et al [69] prepared a Sn-doped Bi 2 WO 6 catalyst, which showed a larger specific surface area and more active sites. The degradation rate of methylene blue increased by 11.4%, and the degradation rate of methylene blue reached 92% when the doping rate of Sn was 2%.…”
Section: Metal Dopingmentioning
confidence: 99%
“…With the development of the circular economy, the present wastewater treatment was designed with the philosophy of a low–carbon economy and environment–friendly to reduce energy consumption, emission of greenhouse gases, and waste generation [ 1 , 2 ]. Serious pollution of the water environment was assigned as the remarkable consequence of rapid global industrial development [ 3 ]. Pharmaceuticals have attracted wide attention due to their splendid competence in repairing for protecting health.…”
Section: Introductionmentioning
confidence: 99%